Human factor parameters influence scaling on professional risk level at engineering facilities - N. O. Kovalkovskaya; V. V. Kuleshov; V. S. Serdyuk; E. V. Bakiko (Омский научный вестник)
The article deals with the workplace safety issues in the machine-building industry taking into account the human factor influence. The significance and quantitative assessment of the human factor influence on the occupational risk level is shown. An integral criterion for assessing the human factor influence on the occupational risk level is proposed, which can be used by specialists in their work. Rating scales «Perception of information», «Decision-making» and «Actions performing» are developed for practical calculations. The empirical and weighted coefficients of the integral criterion parameters reflecting the dependence of the human factor influence on the occupational risk level are determined. A logarithmic dependence between the human factor and the occupational risk level is established.